Comparative characteristics of DNA loop domains rearrangement in glioblastoma multiforme T98G and glioblastoma astrocytoma U373 cell lines under different culture conditions - Svyrydova, K.; Vasylieva, V.; Kropyvko, S.; Afanasieva, K.; Sivolob, A. (Experimental Oncology, 2023)
Summary. Background: The loop domain organization of chromatin, which plays an important role in transcription regulation, may depend on the cell functional state. The aim of this work was to investigate DNA loop reorganization upon functional transitions in two cell lines ‒ glioblastoma multiforme T98G and glioblastoma astrocytoma U373. Materials and Methods: Single cell gel electrophoresis (the comet assay) was used to analyze the kinetics of the DNA loop migration from the nucleoids obtained from the lysed cells. Results: The DNA fraction in the surface loops and the size of these loops were found to be similar in two glioblastoma cell lines. When synthetic processes were inhibited, the migration of a small portion of inner loops was observed in T98G but not U373 cells. In T98G cells, stimulation of cell proliferation and transcription was accompanied by an increase in DNA fraction in the inner loops and an essential increase in the size of these loops. The effect of stimulation was practically absent in U373 cells. However, the linear density of the loops resolved by the comet assay was found to decrease upon stimulation of proliferation in both cell lines. Conclusion: A decrease in the loop density appears to be associated with an intensification of the synthetic processes in cells upon their stimulation.